Seismic analysis of dam-reservoir system using direct coupling - Mandal, Kalyan Kumar; Maity, Damodar (Journal of Structural Engineering, 2025)
The present paper deals with the analysis of the fluid–structure systems considering the coupled effect of elastic dam and the fluid adjacent to it. Both fluid and dam are discretized by eight-node isoparametric elements. In the governing equations, pressure for the fluid domain and displacement for dam are considered as independent nodal variables. A solution technique namely, direct coupled approach for the analysis of dam-reservoir system has been considered to study the elastic effect of dam on dam-reservoir coupled system. In this study, three different modulus of elasticity of dam is considered and the tip displacement of dam, maximum hydrodynamic pressure and different principal stresses are presented for comparative study. This comparative study shows that the flexibility of dam alters the behavior of dam-reservoir system and elastic effect of the structure is necessary in the analysis fluid-structure interaction problem such as seismic analysis of dam-reservoir system.